Patterns of Writing Tests in Science Concepts: Development by Teacher Candidates in Elementary Schools - Hamdu, Ghullam; Hardiyan, Dessy; Yulianto, Ade (International Conference on Elementary Education, 2020)
The lack of teacher attention to the assessment activities, especially in the manufacture and development of written test questions is the background in this study. Though these written test questions are instruments that teachers often use to identify the results of learning that have been done. Therefore, compiling and developing written test questions are one of the abilities that are important to understand. To be able to develop written test questions, especially science well, several things must be considered, namely variations in the form of questions, suitability with the rules and learning objectives and suitability of questions to explore students' higher-order thinking skills. The qualitative descriptive method is used to describe the pattern of written science test questions developed by prospective teachers in elementary schools. Data is done through documentation and interviews. The findings show that the form of written science test questions that are often developed by 50 participants are multiple-choice forms, short entries, and descriptions. Of the 152 questions developed by the participants, it was found that the questions had met the rules in the preparation of each variation of the form of questions and were by the specified learning objectives. However, the 152 questions analyzed did not meet the criteria for the High Order Thinking Skill. Of the four indicators analyzed there are three indicators (variations in form, rules, and suitability of questions with objectives) must have met the criteria while 1 indicator has not been fulfilled (suitability of questions with High Order Thinking Skill)